Overexpression of Prostate Apoptosis Response Protein-4 In Colon Cancer Cells Can Inhibit Metastasis by Upregulating E-cadherin Expression - Jeffrey Nguyen; Christina Leah B. Kline; Natalia Caballero; Rosalyn B. Irby (Journal of Colon And Rectal Cancer, 2015)
Colon cancer has a five-year survival of 64.7%, and about 50,000 people are expected to die from colon cancer this year. Patients with metastatic colorectal cancer have a significantly worse prognosis, a 12.9% five-year survival. This emphasizes the need for strategies to inhibit the growth and metastases of colorectal cancer. Prostate apoptosis response protein 4 (Par-4) is a pro-apoptotic protein that has been shown to mediate apoptosis in response to stimuli, such as chemotherapeutics and radiation. Recombinant Par-4 protein has been shown to reduce the occurrence of Lewis lung carcinoma metastases in-vivo; however, the mechanism by which Par-4 can inhibit metastasis has not been elucidated. In this study, human colon cancer cell lines - SW480 and SW620 - were transfected with Par-4 plasmid or anti-Par-4 shRNA, and the effect on metastasis was examined. Par-4 overexpression inhibited cell migration and invasion, while Par-4 knockdown promoted it. Moreover, the morphology of SW620 cells was altered when Par-4 levels were increased. The change was characteristic of a mesenchymal-to-epithelial transition (MET) in these cells. MET can be induced by upregulation of E-cadherin expression, and RT-PCR and Western blot analyses showed that E-cadherin mRNA and protein levels, respectively, were increased in the Par-4 overexpressing cells concomitant with a decrease in vimentin. The results of this study demonstrate the potential of Par-4 in colon cancer therapy, not only in primary tumors but also in metastatic cells.
Keywords: Colon cancer